UNIVERSAL INFORMATION BLOCKS AS PART OF THE DATABASE MANAGEMENT SYSTEM OF THE OPERATIONAL DUTY SHIFT OF THE СONTROL СENTER IN CRISIS SITUATIONS - A. L. Popov (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives. The aim of the study is to develop a set of interconnected information blocks for the formation, subsequent processing and application of data in the preparation of reporting and functional documents.Method. The choice of regularly used templates as a basis for the development of information blocks. Based on the structure and forms of the selected templates, software modules for information block interfaces have been developed.Result. Based on the results of identifying and analyzing problematic issues in the activities of the operational duty shift for the automation and intellectualization of the activities of specialists, the idea of developing and using universal information blocks as part of a database management system for automated workplaces was proposed. Interfaces of information blocks are included in the composition of each workstation and provide for the processes of: entering, changing, searching and filtering data; Previewing, printing and saving documents. In the development of algorithms, original software solutions were applied: combining data prepared by several specialists, generating document details, transferring information between different workstations, monitoring the availability of documents, accessing the necessary reference information.Conclusion. The introduction of the developed information blocks: “Schedule of SLM duty”, “Requisites”, “Journal of Carriage of Duty”, “Control”, “Reference book” into the complex of automated workplaces of operational duty shift in the Crisis Management Center allows you to refuse as a result of automation from manual filling of text templates and, as a result, reduce labor intensity, increase resource and improve the quality of preparation of operational reporting documents in the event of accidents, emergencies, fires and functions national documents in the mode of daily activities in accordance with the regulatory, job and functional duties of specialists.